“Agent – Environment” Evolution Mechanism of Greenbelt from the Perspective of Complex Adaptive System: A Case Study of Beijing’s Greenbelts - Song LIU; Peiyu SHEN; Dizi LIU; Zhaocheng BAI (Fengjing Yuanlin)
ObjectiveSince the first successful practice in London in the 1930s, greenbelt has become an important land control and land use planning idea. Greenbelts help solve problems related to urban sprawl and provide multiple ecological, social and economic functions that have profound impact on sustainable regional development. In the past century, the construction of greenbelts have been on the rise in the world, but some greenbelts have also encountered a lot of resistance and destruction in the implementation process, and the gap between planning and implementation is large. On the surface, the obstruction of greenbelt construction is the contradiction between green space protection and development and construction, between ecological land and construction land. In essence, greenbelt construction is a long-term game and coordination of land, capital and other resources among multiple stakeholders such as local governments, citizens, economic organizations and social groups. At present, greenbelt is seldom researched from the perspective of “agent – agent” and “agent – environment” interaction and adaptation mechanism between multiple stakeholders and greenbelt system. This research takes Beijing’s greenbelts (the first greenbelt and the second greenbelt) as an example to, according to the “bottom-up” research paradigm of complex adaptive system theory (CAS), depict the adaptation process of multiple agents to promote the evolution of the greenbelt system, and explore the evolution mechanism of greenbelt, so as to seek targeted solutions to optimize greenbelt planning and promote the implementation of greenbelt policies.MethodsBased on the theory of complex adaptive system, the characteristics of the greenbelt system are analyzed from the perspectives of basic characteristics, structural composition and adaptive mechanism. Taking Beijing’s greenbelts as an example, the evolution process of greenbelt is divided into different stages according to the degree of agent emergence, structure complexity and system maturity. At the same time, based on the four characteristics of complex adaptive systems (aggregation, non-linearity, flow and diversity) and three mechanisms (identification, internal model, and block mechanisms), the interaction between multiple agents and the environment is explored.ResultsThe research results show that the construction of the greenbelt system involves the multi-agent system. In the evolution process of Beijing’s greenbelts, multiple agents such as municipal and district governments, village collectives, private enterprises, township governments and citizens have emerged and interacted with each other more frequently. In the embryonic stage, the main agent of greenbelt construction is single, and rapid urbanization in the macro external environment becomes the biggest hindrance of greenbelt construction. In the experiment breakthrough stage, in 1993, Beijing Municipal Government proposed to introduce market mechanism in greenbelt construction. This macro-level external force and rapid urbanization jointly promoted the self-organization process of greenbelt. Private enterprises spontaneously joined the greenbelt construction and interacted with the government and village collective entities to promote the system evolution. In the orderly implementation stage, both external environmental forces and self-organizing forces play a strong role in the evolution of greenbelt. Major social and cultural events, “urban and rural integration”, “quantity reduction and quality and greening improvement” policies, and diversified citizen participation have all promoted the improvement of the self-organizing capability of greenbelt. Top-down macro planning, policy, bottom-up micro agent interaction and self-organization jointly promote the evolution of the greenbelt system.ConclusionThe construction of greenbelt can rely on not only the “top-down” greenbelt policy, but also the self-organization law, namely “guiding” individuals to change their own behavior rules through the external environment in a “bottom-up” manner, thus achieving the goal of greenbelt construction. In order to realize the sustainable development of greenbelt, it is necessary to enhance the initiative and creativity of the government, attach importance to the collaborative governance of multiple agents and enhance the adaptability of multiple stakeholders. Although the implications of the sustainable development of the greenbelt proposed in this research are relevant to Beijing’s greenbelts, the basic conceptual framework of CAS can also be used as the thinking framework for the governance of other greenbelts. At present, the research of greenbelt system based on CAS theory is still in the exploratory stage with many shortcomings. On the one hand, the evolution process of the greenbelt system is only discussed qualitatively, and has not been discussed quantitatively. On the other hand, it mainly discusses the interaction between the agents of the multi-agent system, and the other three subsystems are less discussed. Future research needs to continue to explore the above limitations in order to more comprehensively understand the complexity of the greenbelt system.